Diagnosis and management of primary liver cancer in men. Issue 4 (19th July 2022) - Raptis, Dimitri; Imber, Charles
Abstract : A number of options are available to treat liver cancer, from non‐invasive techniques to surgery. However, as with so many diseases, prevention is the best approach: identification of high‐risk groups and behaviours plays a key role along with strategies to mitigate risk.